Proposal for a constructive alternative with an environmental focus for a subdivision in Cuiabá – MT - Carignani, Gisele; Guebara, Déborah Karen Mansilha (Technical and Scientific Journal Green Cities, 2024)
This work presents a project proposal for the final year of the Architecture and Urbanism course and covers the creation of a condominium, a linear park and a proposal for a healthy house, with less environmentally impacting materials, to serve as a model for the lots. It is a work that was developed through qualitative research including some case studies for references in the project proposal. The problem arises from the analysis of the effects of climate change that are in evidence all over the world today. The strong temperatures, in addition to the estimated forecast for the municipality of Cuiabá MT, have been significantly exceeded. Among the countless possible actions to help alleviate this impact are project proposals aimed at solutions and the use of more sustainable materials and techniques. Thus, from studies aimed at better identifying the climatic conditions of the city of Cuiabá, information was obtained to support the project. Studies were carried out on the city's climate and temperature, as well as its biome and relative air humidity, aspects that directly influence the population's well-being and construction quality. The choice of materials was also evaluated, which helped in making design decisions, with an emphasis on thermal comfort, increasingly appropriating aspects of implementation and construction with less impact on the environment.
Keywords: Condominium; Healthy home; Sustainability